National Income Identity (Y = C + I + G + NX)

GDP = Consumption + Investment + Government Purchase + (exports-imports)

GDP = Consumption + Investment + Government Purchase + (exports-imports)

National Income Identity (Y = C + I + G + NX)

Nominal GDP

(price level)(real GDP)

(price level)(real GDP)

Nominal GDP

L-Index

Computation in Change of Real GDP with initial prices

Computation in Change of Real GDP with initial prices

L-Index

P -Index

Computation in Change of Real GDP with final prices

Computation in Change of Real GDP with final prices

P -Index

Chain Weighting

average of L-Index and P-Index

average of L-Index and P-Index

Chain Weighting

Growth Rate (percentage change per capita)

(Y_{t+1} - Y_{t }) / Y_{t}

(Y_{t+1} - Y_{t} ) / Y_{t}

Growth Rate (percentage change per capita)

Level of Per Capital Income

Y_{(t+1)} = Yt(1+g)

Y_{(t+1)} = Y_{t}(1+g)

Level of Per Capita Income

Constant Growth Rule

Y_{t} = Y_{o}(1+g)^{t}

Y_{t} = Y_{o}(1+g)^{t}

Constant Growth Rate

Standard Scale when graphed looks like

exponential growth

Ratio Scale when graphed looks like

a straight line, linear.

Computation of Growth Rate

g(constant) = (Y_{t} / Y_{o})^{1/t} - 1

g(constant) = (Y_{t} / Y_{o})^{1/t} - 1

Computing growth rate

Growth rate of ratio: z =x/y

g_{z} = g_{x} - g_{y}

g_{z} = g_{x} - g_{y}

Growth rate of ratio: z = x/y

Growth rate of ratio: z =(x)(y)

g_{z} = g_{x} + g_{y}

g_{z} = g_{x} + g_{y}

Growth rate of ratio: z =(x)(y)

Growth rate of ratio: z = x^{a}

g_{z} = (a)(g_{x})

g_{z} = (a)(g_{x})

Growth rate of ratio: z = x^{a}

Production Function: **K = machine; L = workers**

Y = F(K, L) = A(K^{1/3})(L^{2/3})

Y = F(K, L) = A(K^{1/3})(L^{2/3})

Production Function: **K****= machine; L = workers**

Paramter

Input that is generally fixed over time

Input that is generally fixed over time

Paramter

Exogenous Variable

** INPUT** that is allowed to change over time but determined aheaded of time. (POPULATION)

** INPUT** that is allowed to change over time but determined aheaded of time. (POPULATION)

Exogenous Variable

Endogenous Variable

__ OUTCOME__ (determined by supply and demand)

** OUTCOME** (determined by supply and demand)

Endogenous Variable

Potential Output

Measurment of per capita GDP evolvement if prices are completely flexible and resources fully employed

Measurment of per capita GDP evolvement if prices are completely flexible and resources fully employed

Potential Output

Economic Profit

Total Revenue minus Total payments for INPUT

Total Revenue minus Total payments for INPUT

Economic Profit

Accounting Profit

Revenue minus Payment to labor

Revenue minus Payment to labor

Accounting Profit

output per person in equilibrium

y^{*}= (A-bar)(K^{1/3})

y^{*}=(A-bar)(K^{1/3})

output per person in equilibrium

(A-bar)

Productivity Parameter (Total Factor of Production/Residual)

Productivity Parameter (Total Factor of Production/Residual)

(A-bar)

Law of Diminishing Return

All inputs held constant and 1 input increases and tend to a large number, increasing of output diminishes

All inputs held constant and 1 input increases and tend to a large number, increasing of output diminishes

Law of Diminishing Return

Human Capital

Stock or skills that individuals accumulate to make them more productive

Stock or skills that individuals accumulate to make them more productive

Human Capital

Solow Growth Model

Turning exogenous variables into endogenous variables, where capital is accumulated over time

Turning exogenous variables into endogenous variables, where capital is accumulated over time

Solow Growth Model

Capital Accumulation

K_{t+1} = K_{t} + I_{t} - (d-bar)K_{t}

**Inital Capital(t) + investment used for production(t) -depreciation**

Kt+1 = Kt + It - (d-bar)Kt

**Inital Capital(t) + investment used for production(t) -depreciation**

Capital Accumulation

Steady-State level of Capital

y^{*} = ((s-bar)(A-bar) / (d-bar))^{3/2} (L-bar)

y* = ((s-bar)(A-bar) / (d-bar))^{3/2} (L-bar)

Steady-State level of Capital

Steady-State level of Production

y* = (A-bar)^{3/2}(s-bar/d-bar)^{1/2} (L-bar)

y* = (A-bar)^{3/2}(s-bar/d-bar)^{1/2} (L-bar)

Steady-State level of Production

Investment Equation

(Share of Output for investment) - (weighting diff of real interest and MPK)(MPK)

(Share of Output for investment) - (weighting diff of real interest and MPK)(MPK)

Investment Equation

Nominal

Valued at Current Price

Valued at Current Price

Nominal